Effects of temperature and pectin edible coatings with guava by-products on the drying kinetics and quality of dried red guava - Todisco, Katieli Martins [UNESP] (2018)
With the objective of utilizing agro-industrial by-products and enhancing the quality attributes of dehydrated fruits, this study evaluated the effects of edible pectin-based coatings containing disintegrated guava by-products (up to 50% concentration) and drying temperatures (46–74 °C) on the drying kinetics and nutritional properties of dried red guava. Coatings were applied to guava slices prior to hot-air drying. A central composite rotatable design was used to optimize carotenoid and phenolic compound retention. The effects of the edible coating compositions combined with the drying temperatures affected the effectiveness of the film as a barrier to carotenoid oxidation. Total phenolic compound retention, however, was affected only by temperature. Responses were simultaneously optimized, and high carotenoid and total phenolic retentions were obtained at approximately 60 °C with 25% by-product concentration. The effective water diffusivities were mainly affected by temperature. Consequently, the coatings improved nutritional quality without having a major impact on drying times.